An exploration of the influence of spectral model parameters on the accuracy of the rank correlated SLW model. (October 2018) - Webb, Brent W.; Solovjov, Vladimir P.; Andre, Frederic
Highlights: The influence of spectral model parameters on the predictive accuracy of the Rank Correlated SLW model is explored. The ALBDF database has been re-generated, extending the lower limit of the absorption crosssection to 10–7 m 2 /mol. Two methods for specifying the minimum value of the ALBDF in the model spectralconstruction are proposed, with an investigation of the attendant assumptions needed. It is demonstrated that if sufficient numerical resolution is used the model predictions are independent of the specified value of the blackbody source temperature. It appears that optimal predictive accuracy with the fewest gray gases is achieved when the spatial average temperature is selected as the blackbody source temperature. ABSTRACT: This paper explores the influence of spectral model parameters on the accuracy of the Rank Correlated Spectral Line Weighted-sum-of-gray-gases (RC-SLW) model. The range of the Absorption Line Blackbody Distribution Function (ALBDF) database has been extended as part of this work, and the range of the ALBDF database has been studied as it relates to the RC-SLW model construction and prediction accuracy. The study first defines the maximum lower limit of the absorption cross-section in the ALBDF database which produces accurate predictions of total emissivity. It is shown that although the RC-SLW method yields very good accuracy, results may exhibit some sensitivity to the method used to specify the quadrature bounds. The critical need for sufficiently broad ALBDF data is demonstrated. Complete independence of predictions on blackbody source temperature is demonstrated, provided the solution is accurately numerically resolved. Finally, it is shown that accurate predictions may be achieved using the RC-SLW model using just a few gray gases.